Determinants of Primary Nonadherence to Medications Prescribed by General Practitioners Among Adults in Hungary: Cross-Sectional Evaluation of Health Insurance Data - Harsha, Nouh; Kőrösi, László; Pálinkás, Anita; Bíró, Klára; Boruzs, Klára; Ádány, Róza; Sándor, János; Czifra, Árpád (Frontiers in Pharmacology, 2019)
Background: Primary nonadherence to prescribed medications occurs when patients do not fill or dispense prescriptions written by healthcare providers. Although, it has become an important public health issue in recent years, little is known about its frequency, causes, and consequences. Moreover, the pattern of risk factors shows remarkable variability across countries according to the published results. Our study aimed to assess primary nonadherence to medications prescribed by GPs and its associated factors among adults in Hungary for the period of 2012-2015. Methods: Data on all general medical practices (GMP) of the country were obtained from the National Health Insurance Fund and the Central Statistical Office. The ratio of the number of dispensed medications to the number of prescriptions written by a GP for adults was used to determine the medication adherence, which was aggregated for GMPs. The effect of GMP characteristics (list size, GP vacancy, patients’ education provided by a GMP, settlement type (urban or rural), and geographical location (by county) of the center) on adherence, standardized for patients’ age, sex, and eligibility for an exemption certificate were investigated through multiple linear regression modeling. Results: A total of 281,315,386 prescriptions were dispensed out of 438,614,000 written by a GP. Overall, 64.1% of prescriptions were filled. According to the standardized regression coefficients, there was a negative association between standardized adherence and urban settlement type (β= -0.177, p<0.001), higher level of education (β= -0.170, p<0.001), and vacancy of the general practices (β= -0.129, p<0.001). The larger GMP size proved to be a risk factor, and there was a significant geographical inequality for counties as well. Conclusions: More than one-third of the written prescriptions of GPs for adults in Hungary were not dispensed. This high level of nonadherence had great variability across GMPs, and can be explained by structural characteristics of GMPs, the socio-economic status of patients provided, and the quality of cooperation between patients and GPs. Moreover, our findings suggest that the use of the dispensed-to-prescribed medication ratio in routine monitoring of primary health care could effectively support the necessary interventions.